Beyond tuition fees? The legacy of Blair's government to higher education - Lunt, I (2008)
Although the famous Blair mantra 'education, education, education' was applied by his government mainly to the compulsory education sector, there was no shortage of initiatives in Higher Education (HE). The scene was set by the Dearing Report in 1997 which effectively determined the direction of Blair's first term. The second term enabled Blair to pursue further an agenda of public sector reform, yet the simultaneous commitment to market principles of choice and diversity and to social inclusion created major tensions and dilemmas. Funding the expanded HE was the stimulus which led to Dearing, and has continued to be the major challenge of the ten-year period.